Novel sustainable strategies to control Plasmopara viticola in grapevine unveil new insights on priming responses and arthropods ecology. Issue 6 (18th March 2022) - Giudice, Gaetano; Moffa, Loredana; Niero, Marina; Duso, Carlo; Sandrini, Marco; Vazzoler, Loris Francesco; Luison, Massimiliano; Pasini, Enrico; Chitarra, Walter; Nerva, Luca
Abstract: BACKGROUND: Reduction of fungicide consumption in agriculture is globally recognized as a priority. Government authorities are fostering research to achieve a reduction of risks associated with conventional pesticides and promoting the development of sustainable alternatives. To address these issues, in the present study, alternative protocols for the control of downy mildew infection in grapevine were compared to the standard protocol. In the first protocol, only resistance inducers were used, comprising a single formulation with Acibenzolar S ‐methyl, laminarin and disodium‐phosphonate. The second and third protocols followed the standard protocol but substituted phosphonates with phosphorus pentoxide and Ecklonia maxima extract. RESULTS: The results showed that at veraison downy mildew incidence and severity in all tested protocols were significantly reduced compared to nontreated controls on both canopy and bunches. Expression analysis of key genes involved in plant stress response, indicated that the two protocols for phosphites substitution induced a remodulation of salicylic acid (SA) and jasmonic acid (JA), with positive impact on yields. Analysis of the first protocol revealed that the primed state induced a short delay in bunch ripening, with a shift of carbohydrate metabolism to boost the plant defences, involving an upregulation of defence related‐gene, SAR response and a decreased ROS detoxification. Additionally, analysis on the arthropods populations, in parallel with the positive results achieved using alternatives to conventional fungicides, were enriched by those showing the potential of naturally occurring predators of spider mites. CONCLUSION: This study provides practical solutions to reduce the environmental impact of treatments for the control downy mildew in viticulture. © 2022 Society of Chemical Industry. Abstract : We here analyze whether alternative and sustainable protocols for the control of Plasmopara stimulate molecular and biochemical responses in grapevine together with an interesting impact on arthropod ecology.